Las independencias vistas desde las fuentes en lenguas indígenas - Itier, César (2023)
The South American independence process has a little-known facet: the production, both by the pro-independence creoles and by the royalists, of texts in Quechua and Aymara for the Andean populations, in order to adhere them to one cause or another. Said textual production in native languages was unprecedented since the times of the evangelization of the Andes in the 16th century, but it had to dialogue with their concepts and terms in order to refine the messages of royalists and independentists and better communicate them to the native populations. Such a communication effort on the part of the State would not be seen again in the Andes for a long time.